Enrique Maluku: Sang Petualang Manise dari Kepulauan Rempah - Zoe, Toby; Dyaksa, Velmi Dian Dana; Rabani, La Ode (Universitas Hamzanwadi, 2024)
Reading this novel stimulates curiosity about maritime history and culture. Through the reader's point of view, reading this book makes us feel as if we are little Enrique who is being told and taught by Datuk Harun Abbas about the story of his adventure in a distant land. Appreciation to the author of the novel Clavis Mundi, especially Reinhard Tawas, who brought this topic to the surface and introduced the figure of Enrique in the stage of maritime history not only of the Malay world but also of world maritime history. In the end, Enrique's confession is immortalized in the following stanza “Moluccas, su majestad. And I am not a slave [I am Moluccan, your majesty. And I am not a slave].